FAQ Automated Information System (FAQAIS) development by applying keyword based information retrieval technique / Irsyad Aljuhari Ismail Aljuhari - Ismail Aljuhari, Irsyad Aljuhari (2017)
The development of this project is meant for the students of UiTM Melaka Kampus Jasin. Through an observation that has been conducted, it is found that there is an inefficiency of information management effectiveness in the current process which is through the website and induction programs dissemination. Moreover, the difficulties in having a responsive way of organizing and perceiving information accuracy upon enquired question has been found out during the interview conducted which to assist in information management by using the social media platforms such as Twitter, Facebook and Instagram that calls for the development of FAQ automated Information System (FAQAIS). FAQAIS is a search engine based information system. In FAQAIS, a keyword extraction helps in extracting keywords from a various styles of questioning search term’s sentences. Keyword matching are used align with keyword extraction in developing the system as every extracted search term’s keywords are matched to any similar keyword with a strong similarity rate from the database. If none of the keywords which is the current question enquired matched to any relevant keywords to be retrieved, it will be recorded as a missing query question and be revised by the expert for any relevant solution. The findings and analysis was carried out and the objectives of this project is met and tally with the phases in methodology. The methodology used to assist this project is the Waterfall System Development Life Cycle, which contains 4 phases; Requirement Gathering Analysis, Knowledge Acquisition, Design as well as Implementation. One of the deliverables from the phases is the Software Requirements Specification that is the basis in producing the design documentation. Future enhancement to the system may include the centralized of the system throughout UiTM Malaysia and platform that is hybrid for its access mobility.